Ironi dan Metafora sebagai Kritik Sosial dalam Puisi “Mayat Politik Ditutupi Koran Pagi”: Telaah Stilistika - Masnita Massaguni; Budi Hartono (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The poem “Mayat Politik Ditutupi Koran Pagi” by Afrizal Malna presents sharp social and political criticism through the use of irony and complex metaphors. This study aims to examine how these two linguistic devices are employed to reveal the socio-political realities of post-reform Indonesia. Using a stylistic approach, the research explores the forms, functions, and meanings of irony and metaphor that appear within the poem’s structure. The analysis shows that irony serves to express dissatisfaction and satire toward political conditions that appear orderly but are actually filled with deception and manipulation. Meanwhile, metaphor provides a symbolic depiction of the role of mass media as an instrument of power that conceals the true political reality behind public discourse. Through the interplay of these two stylistic elements, Afrizal Malna succeeds in presenting a poetic representation of society’s anxiety over media domination and the blurring line between truth and political interest. This study is expected to enhance the understanding of literature’s role as a reflective and critical medium in uncovering the relationship between language, power, and ideology within Indonesia’s socio-political dynamics.